2022
DOI: 10.1039/d1tc04997f
|View full text |Cite
|
Sign up to set email alerts
|

Vat dyes: promising biocompatible organic semiconductors for wearable electronics applications

Abstract: The smart healthcare approach requires continuous monitoring of the individual’s specific health parameters to enable disease diagnostics and treatment at early stages. From that viewpoint, wearable electronics, especially electronic skin...

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
7
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 13 publications
(7 citation statements)
references
References 55 publications
(64 reference statements)
0
7
0
Order By: Relevance
“…Currently, the research on biocompatibility of OSCs for bioelectronic applications is in its embryonic stage, and the scarcely available data is often incomplete. [287] So far, biocompatibility studies have been investigated for polythiophene derivatives, such as PEDOT, [288,289] P3HT, [290][291][292] polyaniline, [293] and polypyrrole. [294] Among these, PEDOT has proven to be biocompatible in vivo while introduced in a nerve interface that remained stable for over 7 months.…”
Section: Active Semiconductorsmentioning
confidence: 99%
See 1 more Smart Citation
“…Currently, the research on biocompatibility of OSCs for bioelectronic applications is in its embryonic stage, and the scarcely available data is often incomplete. [287] So far, biocompatibility studies have been investigated for polythiophene derivatives, such as PEDOT, [288,289] P3HT, [290][291][292] polyaniline, [293] and polypyrrole. [294] Among these, PEDOT has proven to be biocompatible in vivo while introduced in a nerve interface that remained stable for over 7 months.…”
Section: Active Semiconductorsmentioning
confidence: 99%
“…More recently, Chetyrkina et al studied the biocompatibility of five different vat dyes commonly used for textile coloration, as prospective OSCs for wearable and on-skin electronics. [287] The authors systematically studied the biocompatibility of the vat dyes by analyzing diverse parameters such as cell count, cell morphology, DNA damages, formation of reactive oxygen species and inflammatory response. Human embryo lung fibroblast cells were incubated in direct contact with thin films of studied OSCs for up to 14 days, and the results indicated that two of the dyes-vat blue 20 and vat orange 9, were almost nontoxic since the response of cells was very similar to control samples.…”
Section: Active Semiconductorsmentioning
confidence: 99%
“…Organic electronics related to semiconductors based on fullerene chemistry have made remarkable progress. [1][2][3][4][5][6] The most common fullerene derivative in organic electronics is Phenyl-C 61 -butyric acid methyl ester (PCBM). [7][8][9][10] Various similar compounds, such as C 60 , have been synthesized and used as n-type semiconductors.…”
Section: Introductionmentioning
confidence: 99%
“…5(d)], respectively, which have increased by one order of magnitude compared to the OFET with conventional direct contacts, and by two orders of magnitude compared to vacuum-processed Vat 3 thin-film transistors. [10,12] Com-pared with other similar semiconductors, such as Vat orange 9 (1.4 × 10 −4 cm 2 •V −1 •s −1 [35] ), Vat yellow 4 (1.5 × 10 −4 cm 2 •V −1 •s −1 [35] ), indigo (2 × 10 −4 cm 2 •V −1 •s −1 [8] ), Vat yellow 1 (0.012 cm 2 •V −1 •s −1 [11] ), and Vat blue 4 (7.5 × 10 −3 cm 2 •V −1 •s −1 [36] ), the performance of the Vat 3 reported here has great advantages in OFETs. Moreover, the optimized device exhibits a more linear 𝐼-𝑉 curve.…”
mentioning
confidence: 97%